Lunch counter sit-ins : how photographs helped foster peaceful civil rights protests - Smith-Llera, Danielle, 1971- (Captured history., 2019)
Presents a history of the lunch counter sit-in protests of the civil rights movement, particularly the January 31, 1960 lunch counter protest when four college students sat at the counter at the local Woolworth's in Greensboro, North Carolina.